2 Use of "assessment for retreatment with tace (ART)" score to ensure appropriate patient selection: a retrospective review of tace re-treatment in the northern ireland regional tace service. (5th April 2017) - McNeill, L; Stratton, L; Kennedy, PT; Cadden, IS; Cash, WJ; McCorry, R; McDougall, NI
Abstract : Background: The "Assessment for Retreatment with TACE (transarterial chemoembolization)" (ART) score was developed to determine suitability for additional TACE treatment in patients with hepatocellular cancer - it utilises AST, absence of radiological response and Child-Pugh score following initial procedure. Those with a score of <1.5 gain benefit whereas those scoring ≥2.5 do not. Aim: To determine whether the ART score successfully predicted those patients who did and did not have repeat TACE for HCC. Method: Retrospective application of ART score to all patients undergoing TACE at the Royal Victoria Hospital, Belfast from March 2011 until July 2016. Results: 99 patients had TACE during the study period of whom 64 had a second TACE. The ART score was > 2.5 in 22 of the 64 and therefore ART score would have excluded one third of retreatments. Of the 35 patients who just had a single TACE treatment, further TACE was not required in 11 (disease was stable in 8 patients, 2 underwent alternative treatments (1 transplant, 1 segmentectomy) and 1 refused). Of the remaining 24 patients not offered repeat TACE, 18 (75%) had an ART score of ≥2.5 and 6 were deemed unfit for other reasons (2 demonstrated disease progression not accounted for by ART score, 2 had significant comorbidities and 2 experienced complications following the initial procedure). Conclusions: The ART score successfully identified three quarters of patients deemed unsuitable for repeat TACE treatment. However, if applied ART would have excluded one third of patients who had a successful second TACE.